Revolutionizing the Global Stock Market: Harnessing Blockchain for Enhanced Adaptability - Geada, N.; Sood, R; Sidana, A (2024)
In the aftermath of the profound fiscal crisis of 2008, the very foundation of the global financial system came under intense scrutiny. The ensuing crash laid bare systemic vulnerabilities and underscored the urgent need for alternative solutions capable of fostering a more transparent and resilient model. This period of economic turbulence exposed critical flaws in the existing global financial infrastructure, prompting a search for innovations that could instill accountability, security, and transparency. It is against this backdrop of financial upheaval that Revolutionizing the Global Stock Market: Harnessing Blockchain for Enhanced Adaptability explores the solutions poised to redefine the dynamics of the stock market. Revolutionizing the Global Stock Market: Harnessing Blockchain for Enhanced Adaptability strategically addresses the objectives crucial for navigating the complexities of the contemporary business landscape. The focus extends beyond survival to thriving, emphasizing the persistence of big-picture perspectives, adaptability to new productivity approaches, and the importance of clear and consistent communication. These objectives also encompass facilitating avenues for employee feedback, fostering continuous improvement, and constructing business continuity plans with inherent elasticity. By offering both a theoretical and practical foundation, the book aims to be an indispensable resource for organizations, managers, and scholars navigating the potential of blockchain technology in the context of the global stock market. Revolutionizing the Global Stock Market: Harnessing Blockchain for Enhanced Adaptability is designed for a diverse readership encompassing academicians, researchers, industry specialists, and technology enthusiasts. Before delving into the specific chapters, the book lays the groundwork by immersing readers in the historical and systemic issues that precipitated the need for innovative solutions. The recommended topics span from dissecting blockchain's disruptive potential to scrutinizing the implications of algorithmic bias in financial services. With chapters dedicated to machine learning algorithms, blockchain adoption in various exchanges, and the interplay between technology and the stock market, this book serves as an essential guide for those seeking a deeper understanding of the transformative power of blockchain technology.